Single‐cell analysis reveals heterogeneity in onset of transgene expression from synthetic tetracycline‐dependent promoters. Issue 2 (6th February 2015) - Rand, Ulfert; Riedel, Jan; Hillebrand, Upneet; Shin, Danim; Willenberg, Steffi; Behme, Sara; Klawonn, Frank; Köster, Mario; Hauser, Hansjörg; Wirth, Dagmar
Abstract Synthetic promoters have been designed for mammalian cells to achieve both temporal and quantitative control over transgene expression without interfering with the endogenous cellular network. Routine applications of synthetic expression systems are based on steady‐state measurements of gene expression while the mechanism by which these steady‐states are realised at the single‐cell level has not been investigated. We focused on the elucidation of the kinetics of doxycycline‐controlled synthetic modules as a paradigm. Following gene expression in single cells, we observed a gradual increase of transgene expression within the first 48 h after activation, as determined by flow cytometry. Time‐lapse microscopy revealed that the onset of transgene expression was highly variable in individual cells. Interestingly, a bidirectional cassette design showed significantly reduced cell‐to‐cell heterogeneity in expression. Of note, the influence of the cell cycle seems to be negligible, since the onset of expression correlates with cell division in only a minor fraction of the cell population. In contrast, rapid and synchronous transgene expression could be realized using a posttranslational regulation system that relies on ligand‐induced stabilization of a tagged protein. Thus, the inherent temporal variability of transcriptionally regulated synthetic transgene expression systems has to be considered for kinetic and correlative experimental applications.